Carbon pools in six-years-old planted and naturally regenerated Acacia mangium stands - Tan, Chun Hung (2013)
This study investigated the carbon pools in Acacia mangium stands of six-year old planted and natural regenerated stands at the Bengkoka Forest Plantation, Pitas, Sabah. The soil for the study site was classified into Kumansi Family (Sabah System) and Typic Tropudult (USDA). The objective was to determine the aboveground biomass (AGB) and belowground biomass (BGB), carbon content of the AGB and BGB, as well as the soil organic carbon content (SOC) in the two silviculturally treated Acacia mangium stands. A random systematic sampling method was adopted in the study where two circular plots of 0.25 ha were established in each of the Acacia mangium stands. Within each plot, the diameters at breast height (DBH) of all trees were recorded. The shrub and organic layers were quantified at five randomly selected positions in each plot. Five litter traps (1 m x 1 m) were set up at the same position as the shrub and organic layer. Three quadrates (25 cm x 25 cm x 30 cm) were randomly dug for root biomass and carbon content. The soil bulk density was determined by using undisturbed soil samples that were collected by using 51 mm diameter ring (100 ml). The results showed that the total amount of carbon pools was 73.56 (± 5.63) t C ha-1 and 82.40 (± 0.69) t C ha-1 for planted and natural regenerated stands and not statistically different. In comparison, the naturally-regenerated stand supported higher carbon pools compared to the planted stand. This study also found that the major contributor to total carbon pools for both planted and naturally-regenerated Acacia mangium plantations was the AGB followed by SOC.